2021
DOI: 10.1186/s13063-021-05309-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet, Mindfulness-Based Stress Reduction and usual care during pregnancy for reducing fetal growth restriction and adverse perinatal outcomes: IMPACT BCN (Improving Mothers for a better PrenAtal Care Trial BarCeloNa): a study protocol for a randomized controlled trial

Abstract: Background Fetal growth restriction (FGR) affects 7–10% of all pregnancies resulting in a higher risk of perinatal morbidity and mortality, long-term disabilities, and cognitive impairment. Due to its multifactorial etiology, changes in maternal lifestyle, including suboptimal maternal diet and stress, have increasingly been associated with its prevalence. We present a protocol for the Improving Mothers for a better PrenAtal Care Trial Barcelona (IMPACT BCN), which evaluates two different mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The pandemic cohort was compared to a previous cohort of pregnant women recruited between February 2017 and October 2019 before the COVID-19 pandemic [19] (Table A1).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The pandemic cohort was compared to a previous cohort of pregnant women recruited between February 2017 and October 2019 before the COVID-19 pandemic [19] (Table A1).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Therefore, it is vital to evaluate the antibiotic resistance properties of bacteria. Furthermore, the development of the intestinal tract is significant in infants; immature intestines and slow intestinal immune development were associated with the high risk of postpartum growth restriction, lactose intolerance, allergy, necrotizing enterocolitis, and other intestinal related diseases ( Zhuang et al, 2019 ; Osorio, 2020 ; Crovetto et al, 2021 ). Studies confirmed that probiotics were beneficial to intestinal development, intestinal epithelial renewal, and intestinal mucosa balance ( Blumberg and Gensollen, 2017 ; Zhuang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has shown the positive effects of the Mediterranean diet (MD) on health outcomes (i.e., lower incidence of cardiovascular and metabolic diseases, lower incidence of neurodegenerative diseases, lower incidence of multiple cancer sites, and lower mortality) [23][24][25][26]45]. The traditional Mediterranean diet is a plant-oriented dietary pattern characterized by a high intake of vegetables, fruit, whole grains, legumes, and nuts; a moderate intake of dairy products (mostly cheese and yoghurt); a moderate intake of fish and poultry; a low intake of red meat; a high intake of extra-virgin olive oils, used as the main source of fat; and a moderate intake of wine, consumed with meals [46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent research findings pointed out suboptimal maternal diet [23][24][25] and maternal stress as potentially important contributors [26]. We hypothesize that the analysis of the placental histology might contribute to differentiate the phenotypes of HDP and of FGR as well as their possible overlapping in the real-life clinical scenario.…”
Section: Introductionmentioning
confidence: 89%